Trade relations in the XXI century : challenges facing the Association of Caribbean States - SELA (SELA CaracasVE, 1995)
Focuses attention on the problems and opportunities facing the Member States of the Association of Caribbean States (ACS) with regard to trade, at the regional, subregional, hemispheric and multilateral levels, and on the types of measures which should be undertaken to compete in the fields of trade and investment. Describes the steps already undertaken within Latin America and Caribbean organizations, within the OAS and with respect to Latin trade to help ACS countries prepare themselves to face the trade challenges of the future.